Addition of clonidine to bupivacaine in transversus abdominis plane block prolongs postoperative analgesia after cesarean section - Ranju Singh; Nishant Kumar; Aruna Jain; Sudipta Joy (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: The aim was to compare duration of postoperative analgesia with addition of clonidine to bupivacaine in bilateral transversus abdominis plane (TAP) block after lower segment cesarean section (LSCS). Material and Methods: One hundred American Society of Anesthesiologists (ASA) grade I and II pregnant patients undergoing LSCS under spinal anesthesia were randomly divided to receive either 20 ml bupivacaine 0.25% (Group B; n = 50) or 20 ml bupivacaine+1ug/kg clonidine bilaterally (Group BC; n = 50) in TAP block in a double-blind fashion. The total duration of analgesia, patient satisfaction score, total requirement of analgesics in the first 24 h, and the side effects of clonidine such as sedation, dryness of mouth, hypotension, and bradycardia were observed. P < 0.05 was taken as significant. Results: In 99 patients analyzed, TAP block failed in five patients. Duration of analgesia was significantly longer in Group BC (17.8 ± 3.7 h) compared to Group B (7.3 ± 1.2 h; P < 0.01). Mean consumption of diclofenac was 150 mg and 65.4 mg in Groups B and BC (P < 0.01), respectively. All patients in Group BC were extremely satisfied (P < 0.01) while those in Group B were satisfied. Thirteen patients (28%) in Group BC were sedated but arousable (P = 0.01) compared to none in Group B. In Group BC, 19 patients complained of dry mouth compared to 13 in Group B (P = 0.121). None of the patients experienced hypotension or bradycardia. Conclusion: Addition of clonidine 1 μg/kg to 20 ml bupivacaine 0.25% in TAP block bilaterally for cesarean section significantly increases the duration of postoperative analgesia, decreases postoperative analgesic requirement, and increases maternal comfort compared to 20 ml of bupivacaine 0.25% alone.